Navigable Intraoperative Ultrasound and Fluorescence-Guided Resections Are Complementary in Resection Control of Malignant Gliomas: One Size Does Not Fit All - Moiyadi, Aliasgar; Shetty, Prakash (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Introduction Conventional imaging (intraoperative ultrasound and intraoperative magnetic resonance imaging) as well as enhanced visualization (aminolevulinic acid [ALA]-based fluorescence-guided resection) have both been used to improve the resection of malignant gliomas. Each modality has its pros and cons and may not be suitable for all cases. We describe our experience with these two complementary techniques.Methods Eight patients underwent resection for malignant gliomas using combined navigable three-dimensional ultrasound (3D-US) and ALA-induced fluorescence. These were analyzed for magnetic resonance imaging characteristics, resectability, and extent of resection. The utility of navigable 3D-US and the fluorescence were assessed for each case to stratify cases that may benefit from either or both of these techniques.Results Four subjects had predominant contrast-enhancing potentially resectable gliomas. Intraoperative strong fluorescence was seen, which was the primary guide for resection control. Navigable 3D-US was additionally useful for planning the craniotomy and localizing the subcortical lesions. All four tumors were gross-totally excised. Four other tumors were minimally enhancing and diffuse. Fluorescence was patchy and not used for resection control; instead, navigable 3D-US was the primary guide for resection. However, the fluorescence helped locating the focally higher grade parts within the tumors. Gross-total resection could be achieved in one patient.Conclusions Navigable 3D-US and ALA-induced fluorescence provide information regarding different aspects of tumor extent and combined together enhance the extent of resection. Fluorescence-guided resection may be sufficient for enhancing tumors, but nonenhancing tumors are better resected with navigable 3D-US.
Keywords: navigable ultrasound; fluorescence; malignant gliomas; combined modality; resection control